Distributional biases in the analysis of climate change - Peter Skott; Leila Davis (University of Massachusetts, Department of Economics, 2011)
The economic analysis of global warming is dominated by models based on optimal growth theory. These representative-agent models have an intrinsic distributional bias in favor of the rich. The bias is compounded by the use of revenue-neutrality in the allocation of emission permits. The result is mitigation recommendations that are biased downwards.
Keywords: Q13; I3; E1; 330; representative agent; welfare; global warming; inequality.